Tobacco prevention policies in west-African countries and their effects on smoking prevalence - Winkler, Volker; Lan, Yong; Becher, Heiko (BMC public health, 2015)
The WHO Framework Convention on Tobacco Control was shown to effectively lower smoking prevalence in in high income countries, however knowledge for low and middle income settings is sparse. The objective of this study was to describe WHO MPOWER policy measures in thirteen West-African countries and to investigate their correlation with smoking prevalence.
Gesehen am 02.07.2020